Beyond antibodies: New affinity reagents to unlock the proteome. Issue 6 (20th February 2014) - Lollo, Bridget; Steele, Fintan; Gold, Larry
Abstract : Antibodies have been the workhorse reagents of protein capture and quantification since their 1959 debut in the RIAs developed by Yalow and Berson. However, there are technical challenges to the use of antibodies in highly multiplexed arrays aimed at measuring hundreds or even thousands of proteins at one time. We describe here a recently developed class of synthetic protein‐binding reagents (slow off‐rate modified aptamer). We discuss the chemical makeup and protein binding specifications of slow off‐rate modified aptamer reagents, compare them to traditional aptamers and antibodies, briefly describe the novel proteomic assay that takes advantage of their unique properties, and provide several examples of their multiple applications to biomarker discovery and validation across a range of biomedical science questions.